2006
DOI: 10.1097/00011363-200610000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Predicting English Word Reading Skills for Spanish-Speaking Students in First Grade

Abstract: This article describes the word reading skills in English and Spanish for a sample of 244 Spanish-speaking, English-learning (hence, bilingual) students in first grade and presents a predictive model for English word reading skills. The children in the study were assessed at the end of kindergarten and first grade, respectively. Data were gathered with 3 subtests of the Woodcock Language Proficiency Battery and a researcher-developed phonological awareness task. Results showed that, on average, children's Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
41
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 20 publications
5
41
0
Order By: Relevance
“…Findings revealed that many Spanish/English bilingual students are progressing more slowly than their English monolingual peers particularly in their English oral language abilities. Although many of these children have been shown to lag behind their peers in both English and Spanish (Tabors et al, 2003), this sample of children was particularly behind in English vocabulary knowledge in kindergarten (Tabors et al, 2003) and first grade (Páez & Rinaldi, 2006). Somewhat lower vocabulary may be expected when children are learning two languages; however, when vocabulary is limited it is likely that children will experience problems learning to read (Dickinson, McCabe, Anastasopoulos, PeisnerFeinberg, & Poe, 2003).…”
mentioning
confidence: 92%
“…Findings revealed that many Spanish/English bilingual students are progressing more slowly than their English monolingual peers particularly in their English oral language abilities. Although many of these children have been shown to lag behind their peers in both English and Spanish (Tabors et al, 2003), this sample of children was particularly behind in English vocabulary knowledge in kindergarten (Tabors et al, 2003) and first grade (Páez & Rinaldi, 2006). Somewhat lower vocabulary may be expected when children are learning two languages; however, when vocabulary is limited it is likely that children will experience problems learning to read (Dickinson, McCabe, Anastasopoulos, PeisnerFeinberg, & Poe, 2003).…”
mentioning
confidence: 92%
“…Findings from the ECS showed that many Spanish/English bilingual students lag behind monolingual children of the same age in their oral language abilities in English and Spanish (Páez, Tabors, & López, in press;Tabors, Páez, & López, 2003). In particular, English vocabulary skills were limited for children in the ECS sample when they were first assessed at 4 years of age (Páez et al, in press), with low levels of vocabulary and gaps between monolingual norms and the sample persisting through first grade (Páez & Rinaldi, 2006). These findings are consistent with those of recent studies with similar populations of Spanish/English bilingual students that have found these students' oral language, in particular vocabulary knowledge, to lag significantly behind that of their English-speaking peers (August et al, 2005;Lindsey, Manis, & Bailey, 2003;Manis, Lindsey, & Bailey, 2004).…”
mentioning
confidence: 99%
“…M. López & Greenfield, 2004;Páez & Rinaldi, 2006;Rinaldi & Páez, 2008). However, because young DLLs may not learn new English words, letter names, or letter sounds in the same incidental way as monolingual children, it is particularly important for preschool and kindergarten teachers to provide intentional and explicit instruction related to these areas.…”
Section: Instructional Strategies To Support Young Dlls' Language Andmentioning
confidence: 99%
“…A. Collins, 2014;Hammer et al, 2014;Hoff, Rumiche, Burridge, Ribot, & Welsh, 2014;Isbell, 2002;E. A. Ortiz, 2009;Saffran, Senghas, & Trueswell, 2001).Because of the variety of contributors to this process, when a young Hispanic DLL first participates in an early education program, his or her linguistic proficiency may vary from minimal in both languages; fluent in Spanish, but not in English; competent in everyday English social conversations, but not in the type of language used in classrooms to learn different academic subjects (and often referred to as academic language); to fully proficient in both languages (Espinosa, 2008;Genesee, 2010;Grant, 1995;Oades-Sese, Esquivel, Kaliski, & Maniatis, 2011;Páez & Rinaldi, 2006;Place & Hoff, 2011;Tabors & Snow, 2001).Data from national surveys also supports the link between home language environments and uneven Hispanic DLL proficiency in speaking and understanding English upon school entry. In 2000, an estimated 75% of Hispanic children in immigrant families were living with at least one parent who did not speak English exclusively or very well, and half lived with two parents with limited English skills (Hernandez, 2006).…”
mentioning
confidence: 99%